Класстан тыс жумысларда үлке материалларынан пайдаланыўдың тәлим –тәрбиялық әҳмийети - Баўетдинов, Р.А (SCIENCE and SOCIETY, 2019)
This article is about the educational and moral meaning of using archaeological findings in extracurricular work. There is given an analysis to the kinds and methods of using regional materials in extracurricular work. The author of the article emphasizes the positive
Keywords: extracurricular works; history; historical sources; material sources; historical memory; archaeological findings; excursion classes; museum exhibits